PENINGKATAN KAPASITAS PENGELOLAAN BUMDES MELALUI PELATIHAN PENGEMBANGAN POTENSI UNGGULAN DESA DI KECAMATAN AMONGGEDO KABUPATEN KONAWE - Moita, Sulsalman; Nusantara, Ambo Wonua; Tuwu, Darmin; Liwaul, Liwaul; Sarpin, Sarpin; Azizah, Lutfiana Nur (Universitas Halu Oleo, 2023)
The objectives of the Internal Community Partnership Program (PKMI) are: 1). Increasing the knowledge and technical skills of BUMDes managers in developing superior village potential through planning business types and actively involving the community as beneficiaries; and 2). Increase the knowledge and morality of BUMDes managers, so that in developing the village's superior potential they can utilize budgets that are carried out honestly, openly, fairly, professionally and future-oriented. To achieve this goal, the method used was training with a focus on lecture and FGD methods. The PKMI results show that: 1) Training to increase the capacity of BUMDes managers in developing superior village potential, is a vehicle for administrators and business unit managers to identify and ensure appropriate, effective and innovative superior potential in supporting BUMDes programs to increase village income and community welfare; 2) Capacity building training in developing superior village potential becomes a starting point for administrators, business managers and BUMDes program target groups to identify various challenges and obstacles; as well as solving problems, so that they are able to choose the right type of business by involving the community as beneficiaries.